Changes of stride pattern of world class 400-m hurdlers - reasons and consequences - Iskra, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction Stride pattern (less accurate hurdles rhythm) is an important aspect of technical preparation in 400-m hurdling (400m H) - McFarlane (2000). The number of strides between following hurdlers depend on gender, sport level, somatic parameters, motor and technical abilities and other, sometimes objective factors (Iskra 1999, Jarver 2004, Ditroilo & Marini 2004). The aim of this study was to find the main reasons and effects of changes of strides pattern in male 400m H. Methods In this investigation the author examined 400m H races from the greatest athletic competitions (especially Olympic Games, World and European Championships) in the period between 1968 and 2004. The data were compiled by previous biomechanical researches and official reports from above meetings. Altogether the study analysed 120 individual races of best hurdlers in the world (age; 25.9±3.5 years; personal best: 48.51±0.81s). From races researchers eliminated all "one-leg" hurdlers (13 or 15 strides rhythm) and unspecific, occasional types of run (e.g. from 14 to 17 strides). Finally the authors separated 104 athletes into four most popular types of strides pattern: A ("single alternate"/13 to 14 strides; n=27), B ("paired alternate"/13-14-15strides; n=25), C ("double step down"/13 to 15 strides; n=25) and D ("single alternate", variant 2/14 to 15 strides; n=27). The data consisted of somatic parameters (body height, Rohrer`s indicator), personal best results (both 400m H and 400m flat), technical indicator, split times between three parts of run (t1-4, t4-7, t7-10), number of strides when athlete changed the rhythm, and times of interhurdle spaces before and after the change of stride rhythm. One -way analysis of variance (ANOVA) with Tuckey`s test was performed to examine the significance of group differences (p 0.05). Results The best results in 400m H were achieved by hurdlers from group A. Type of body build (Rohrer`s indicator) and technical preparation (400m H - 400m flat) did not differ significantly between all groups (accordingly: F=0.24 and 2.11, p 0.05). Body height and personal running achievements were similar in the first three groups; only hurdlers from group D were shorter and had poorer results. There were significantly important differences in all three stages (beginning, middle and final) of the distance. The greatest differences were in the second (t4-7) part of the run (F=8.56, p 0.001). In the initial part of race (t1-4) there were no differences only between group A and B; in the last part (t7-10) we did not observe differences between groups B,C and D. An average change of hurdles rhythm was 5-6 (B) or 6-7 (A,C,D) hurdle, on the second curve. The results before the change of stride pattern in the hurdle unit (=distance between two hurdles) and after the hurdle clearance were similar in groups A,C,D, significantly different from group B. Conclusions Type of stride pattern of world class hurdlers does not depend on somatic parameters and special motor preparation. Each type of stride rhythm in 400m H was characterised by a specific, temporal (time of each parts of race) and special (number of strides and place of changes) during the plan of the race.